Power controllable gain switched fiber laser at ~ 3 μm and ~ 2.1 μm - Yiwen Shi (Nature Portfolio, 2021)
Abstract Based on a hybrid pumping method consisting of a 1150 nm continuous-wave pump source and a 1950 nm pulsed pump source, we demonstrate a power controllable gain-switched fiber laser in dual wavebands at ~ 3 μm and ~ 2.1 μm. Different pumping schemes for pumping a Ho3+-doped ZBLAN fiber are studied. Using only the 1950 nm pulsed pump source, ~ 2.1 μm gain-switched pulses with single and double pulses are obtained separately at different pump powers. This phenomenon indicates that the 1950 nm pulsed pump source acts as a modulator to trigger different states of the ~ 2.1 μm pulses. Moreover, by fixing the 1150 nm pump power at 3.259 W and adjusting the 1950 nm pump power, the output power of the ~ 2.1 μm gain-switched pulsed laser is flexibly controlled while the ~ 3 μm laser power is almost unchanged, inducing the maximum output powers of 167.96 mW and 260.27 mW at 2910.16 nm and 2061.65 nm, respectively. These results suggest that the comparatively low power of the ~ 2.1 μm gain-switched pulsed laser in dual-waveband laser can be efficiently overcome by reasonably controlling the 1950 nm pump power.